014. Localized Meconium Peritonitis Due to Perforation of Ileum Atresia: Case Report - Amalia, Gina; Wardhani, Avriana Pety (JBN (Jurnal Bedah Nasional), 2024)
Background : Ileal atresia is a congenital disorder that can cause serious complications such as intestinal obstruction, intestinal ischemia, and intestinal rupture. The worldwide incidence rate is 1 in 5,000 - 10,000 births, which can be influenced by various factors such as the use of certain drugs during pregnancy, a family history of similar complaints, and premature birth which can increase the risk. One of the rare features is spontaneous walling off of the abdominal wall which resembles a cyst. From this case we found a patient who had this rare clinical presentation. Case : 3 days old baby was referred to Dr. Kariadi Semarang with a greenish lump in the epigastric region since birth, accompanied by the appearance of small intestinal obstruction. The patient was born via vaginal delivery at 39 weeks' gestation with a normal Apgar score and weight. From the history and examination that had been carried out, it was concluded that there was ileal atresia and an exploratory laparotomy was performed. A green mass was obtained which was the walling off of the ileal perforation. During the operation, another finding was found, ileal perforation caused by atresia and severe adhesions (Grade IV). The patient then underwent the Santulli procedure and laceration repair. Conclusion: Ileal atresia is diagnosed from anamnesis taking from baby has signs of obstruction such as flatulence and vomiting. The incidence of ileal atresia associated with perforation and causing peritonitis is still rare due to lack of reporting of these cases. Peritonitis, which occurs due to intestinal perforation in the jejunoileal segment, can cause the release of intestinal products, meconium, into the intra-abdominal cavity. Spontaneous walling off in this case is quite rare, and because the perforation product is sterile, it does not give a picture of inflammation.